2005
DOI: 10.1111/j.1523-1755.2005.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Low fetuin-A levels are associated with cardiovascular death: Impact of variations in the gene encoding fetuin

Abstract: The present study shows that a low fetuin-A level is associated with malnutrition, inflammation, and atherosclerosis (carotid plaques), as well as with increased cardiovascular and all-cause mortality. Because the present study demonstrates an effect of variations in the AHSG gene on both circulating fetuin-A levels and outcome, this indicates that ESRD patients with the AHSG 256Ser allele are at risk of accelerated vascular calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
241
8
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(284 citation statements)
references
References 42 publications
30
241
8
5
Order By: Relevance
“…There are some studies indicating that the fetuin-A gene polymorphism (c.766C > G) can be associated with reduced serum fetuin-A levels. 20,25 In their cohort study, Osawa et al 29 evaluated the importance of fetuin-A gene polymorphism in chronic renal failure patients and they showed that the patients with c.766C > G polymorphism had significantly lower serum fetuin-A levels and higher all-cause and cardiovascular mortality rates. Aksoy et al 8 showed that patients with CG genotype had lower serum fetuin-A concentrations compared with those carrying CC genotype when fetuin-A c.766C > G polymorphism were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies indicating that the fetuin-A gene polymorphism (c.766C > G) can be associated with reduced serum fetuin-A levels. 20,25 In their cohort study, Osawa et al 29 evaluated the importance of fetuin-A gene polymorphism in chronic renal failure patients and they showed that the patients with c.766C > G polymorphism had significantly lower serum fetuin-A levels and higher all-cause and cardiovascular mortality rates. Aksoy et al 8 showed that patients with CG genotype had lower serum fetuin-A concentrations compared with those carrying CC genotype when fetuin-A c.766C > G polymorphism were examined.…”
Section: Discussionmentioning
confidence: 99%
“…An important relationship between low serum fetuin-A levels and vascular calcification has been confirmed by several other investigators. 18,19,20 Associations between fetuin-A gene polymorphism and calcifications in various tissues such as kidney 8 , coronary artery 21 and bone 22 have been investigated. In the literature, there is no study investigating the relationship between fetuin-A gene polymorphism and dental calculus.…”
Section: Introductionmentioning
confidence: 99%
“…29 Single-nucleotide polymorphisms of the gene encoding AHSG were also shown to affect the serum levels of the protein in different populations. 30,31 Furthermore, an increased consumption was also supposed to result in reduced serum AHSG levels in patients with hematological malignancies. 32 In pregnancy, the fetoplacental unit can be another source of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of all variables with P Ͻ 0.2 (gender, history and current smoking, diastolic BP, use of tacrolimus, azathioprine, and sirolimus, creatinine, total cholesterol, triglyceride, albumin, glutamate oxalacetate transaminase, 25[OH] and 1,25[OH] vitamin D3, angiotensin converting enzyme inhibitor and/or angiotensin receptor blocker treatment, rs2248690 T allele, rs2070635 A allele, rs4918 G allele, and the TCAG haplotype) in a stepwise linear regression analysis showed that the independent determinants of lower serum fetuin-A levels were a lower level of cholesterol, the AHSG rs4918 G allele, and a history of smoking (Table 3). It must be noted that the robust correlation between serum fetuin-A levels and total cholesterol levels was not influenced by the administration of statins in this cohort (Figure 3).…”
Section: Determinants Of Serum Fetuin-a Levelmentioning
confidence: 99%
“…The discrepancy could reflect variable inflammation parameters and the possibility that fetuin-A levels may be determined by inflammation-independent mechanisms, including genetic factors. Of interest, polymorphisms in the AHSG gene impact on fetuin-A level in dialysis patients (25).…”
Section: Introductionmentioning
confidence: 99%